Hubungan COVID-19 dengan Kejadian Persalinan Prematur di RSUD Bandung Kiwari Tahun 2021 - Kamila, Lia (Jurnal Kesehatan Rajawali, 2023)
The number of premature babies born in 2021 at Bandung Kiwari Hospital was 8.7% of 5,447 live births. Based on preliminary data obtained from the Bandung Kiwari Regional Hospital's medical records, the number of premature births in 2021 was 478, the number of premature births with Covid-19 has increased significantly from 2020, namely 112, increasing to 19.3% in 2021. The research aims to analyze the relationship between COVID-19 and the incidence of premature birth at Bandung Kiwari Regional Hospital in 2021. Quantitative research uses an analytical observational type with a case-control approach. The sampling technique uses simple random sampling. The sample for this research consisted of 106 women giving birth at the Bandung Kiwari Regional Hospital in 2021. Data analysis used univariate analysis and bivariate analysis with the chi-square analysis statistical test. The results of the univariate analysis showed that half of the respondents experienced prematurity and half of the respondents did not experience prematurity. There were 36 positive cases of Covid-19 in pregnant women at the Bandung Kiwari Regional Hospital and 70 negative in pregnant women. The results of the bivariate analysis showed that there was a relationship between Covid-19 and the incidence of preterm labor (α value 0.024 < α 0.05). These results show that there is a significant relationship between Covid-19 and the incidence of premature birth.